Rapid and sustained B-cell depletion with subcutaneous ofatumumab in relapsing multiple sclerosis: APLIOS, a randomized phase-2 study. (May 2022) - Bar-Or, Amit; Wiendl, Heinz; Montalban, Xavier; Alvarez, Enrique; Davydovskaya, Maria; Delgado, Silvia R; Evdoshenko, Evgeniy P; Giedraitiene, Natasa; Gross-Paju, Katrin; Haldre, Sulev; Herrman, Craig E; Izquierdo, Guillermo; et al.
Background: Ofatumumab, the first fully human anti-CD20 monoclonal antibody, is approved in several countries for relapsing multiple sclerosis (RMS). Objective: To demonstrate the bioequivalence of ofatumumab administered by an autoinjector versus a pre-filled syringe (PFS) and to explore the effect of ofatumumab on B-cell depletion. Methods: APLIOS (NCT03560739) is a 12-week, open-label, parallel-group, phase-2 study in patients with RMS receiving subcutaneous ofatumumab 20 mg every 4 weeks (q4w) (from Week 4, after initial doses on Days 1, 7, and 14). Patients were randomized 10:10:1:1 to autoinjector or PFS in the abdomen, or autoinjector or PFS in the thigh, respectively. Bioequivalence was determined by area under the curve (AUC τ ) and maximum plasma concentration ( C max ) for Weeks 8–12. B-cell depletion and safety/tolerability were assessed. Results: A total of 256 patients contributed to the bioequivalence analyses (autoinjector-abdomen, n = 128; PFS-abdomen, n = 128). Abdominal ofatumumab pharmacokinetic exposure was bioequivalent for autoinjector and PFS (geometric mean AUC τ, 487.7 vs 474.1 h × µg/mL (ratio 1.03); C max, 1.409 vs 1.409 µg/mL (ratio 1.00)). B-cell counts (median cells/µL) depleted rapidly in all groups from 214.0 (baseline) to 2.0 (Day 14). Ofatumumab was well tolerated. Conclusion: Ofatumumab 20 mg q4w self-administered subcutaneously via autoinjector is bioequivalent to PFS administration and provides rapid B-cell depletion.